Pheochromocytoma in elderly people: case report - Puzhakkal, Shikhil; Veetil, Pradeep Puthen (International Surgery Journal, 2022)
Pheochromocytoma in elderly people is a very rare disease and surgical removal is the only cure. Here we present an 81-year-old gentleman with multiple co morbidities with left adrenal incidentaloma. He was diagnosed to have left pheochromocytoma with biochemical evaluation. He underwent laparoscopic adrenalectomy after a prolonged preparation with alpha and beta blockers. This is the second oldest patient with histo-pathological diagnosis of pheochromocytoma. So high index of suspicion is needed to diagnose pheochromocytoma and a prolonged preoperative preparation is required in elderly patients. As he had high pheochromocytoma of adrenal scaling score (PASS), he is under close follow up.